Stakeholder perceptions of marine plastic waste management in the United Kingdom - McNicholas, Grace; Cotton, Matthew (Ecological economics, 2019)
Plastic pollution is a significant threat to the marine environment. The problem has become subject to increasing scientific scrutiny, media campaigning and growing public awareness. This has stimulated policy-makers to introduce changes aiming to reduce plastic consumption and production. However, in order to arrive at socially acceptable policy and behaviour change solutions, we need to better understand the diverse array of stakeholder perspectives on ocean plastic pollution, economic policy and consumption responsibilities. We employ a Q-methodological study to research key stakeholder viewpoints from ENGO, government agency, plastic manufacturer, retailer, research and citizen representatives in the UK. We find four emergent types of perspectives surrounding this topic, labelled: a) socio-cultural visibility and responsibility, b) dragons of inaction – disempowerment and defeatism, c) value-action gap, d) refuting retailer responsibility. We also identify a clear consensus that current and proposed government policy is not radical enough – the focus needs to move beyond single-product taxes and levies on disposal items (e.g. bags, coffee cups), to a deeper reflection about public awareness raising and education, defining waste responsibilities more clearly, and working to change the habits and unsustainable practices of consumers in the face of public apathy and a resistant retail environment. •Marine plastic pollution is a growing issue in current environmental discourse in the United Kingdom and across Europe•The UK Government is proposing tax measures to reduce plastic consumption, thus social scientific research is key•We employ Q-methodology to explore the differences in perspectives that emerge between competing stakeholder interests•We reveal four distinct discourses and conclude policy must stimulate public responsibility towards plastic consumption